A protective effect of the BDNF Met/Met genotype in obesity in healthy Caucasian subjects but not in patients with coronary heart disease - Sustar, A; Nikolac Perkovic, M; Nedic Erjavec, G; Svob Strac, D; Pivac, N (European review for medical and pharmacological sciences, 2016)
Brain-derived neurotrophic factor (BDNF) is a neurotrophic factor with an important role in the regulation of body weight, body mass index (BMI) and obesity. Increased BMI that leads to obesity is a substantial risk factor for coronary heart disease (CHD). The functional BDNF Val66Met polymorphism (rs6265) has been associated with CHD, obesity and BMI. The aim of the study was to determine the association between BDNF rs6265 polymorphism and CHD and/or BMI in patients with CHD and healthy control subjects. The study included 704 Caucasian subjects: 206 subjects with CHD and 498 healthy control subjects. The BDNF rs6265 genotype frequency was similar in male and female subjects, and there were no differences in the frequency of the BDNF rs6265 genotypes in 206 patients with CHD and in 498 healthy subjects. When study participants were subdivided according to the BMI categories into normal weight, overweight and obese subjects, significantly different BDNF rs6265 genotype frequency was found within healthy subjects, but not within patients with CHD. Healthy subjects, but not patients with CHD, subdivided into carriers of the Met/Met, Met/Val and Val/Val genotype, had different BMI scores. The BDNF rs6265 genotype frequency was similar in male and female subjects, and there were no differences in the frequency of the BDNF rs6265 genotypes in 206 patients with CHD and in 498 healthy subjects. When study participants were subdivided according to the BMI categories into normal weight, overweight and obese subjects, significantly different BDNF rs6265 genotype frequency was found within healthy subjects, but not within patients with CHD. Healthy subjects, but not patients with CHD, subdivided into carriers of the Met/Met, Met/Val and Val/Val genotype, had different BMI scores. BDNF rs6265 polymorphism was not associated with a diagnosis of CHD or with BMI categories among patients with CHD. In contrast, healthy Caucasians, carriers of the BDNF Met/Met genotype, had more frequently normal weight compared to carriers of other BDNF genotypesBDNF rs6265 polymorphism was not associated with a diagnosis of CHD or with BMI categories among patients with CHD. In contrast, healthy Caucasians, carriers of the BDNF Met/Met genotype, had more frequently normal weight compared to carriers of other BDNF genotypes. BDNF rs6265 polymorphism is associated with BMI categories, and the BDNF Met/Met genotype has a protective role in obesity in healthy subjects, while this effect was not present in patients with CHD.